2022
DOI: 10.1371/journal.pgph.0001317
|View full text |Cite
|
Sign up to set email alerts
|

Improved diagnosis of extrapulmonary tuberculosis in adults with and without HIV in Mbeya, Tanzania using the MPT64 antigen detection test

Abstract: Extrapulmonary tuberculosis (EPTB) in People Living with HIV (PLWHIV) is a diagnostic challenge. Our immunochemistry based MPT64 antigen detection test has shown improved sensitivity compared to current laboratory tests in the resource limited diagnostic setting. The aim of this study was to validate the implementability and diagnostic performance of the test in PLWHIV and HIV negative adults in a HIV endemic Tanzanian setting. Adult (>18 y) presumptive EPTB patients were prospectively enrolled at Mbeya Zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
1
3
1
Order By: Relevance
“…The sensitivity of the MPT64 test in cytology specimens was low in our study (36%), contrasting the results of our previous studies, which showed sensitivities of 69–92% [ 18 , 19 , 20 ]. This could be explained by the difference in primary polyclonal antibodies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of the MPT64 test in cytology specimens was low in our study (36%), contrasting the results of our previous studies, which showed sensitivities of 69–92% [ 18 , 19 , 20 ]. This could be explained by the difference in primary polyclonal antibodies.…”
Section: Discussioncontrasting
confidence: 99%
“…The test method is rapid and robust, and its relative simplicity makes it suitable for implementation in low‐resource settings with modest laboratory facilities. Recent results from validation of the MPT64 test in routine diagnostics in the resource‐limited and high TB burden areas of Zanzibar and Tanzania show sensitivity and specificity of 69–92% and 78–95%, respectively, against a composite reference standard (CRS) [ 18 , 19 , 20 ]. However, the antibodies evaluated in previous studies were in limited supply.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, a negative MPT64 test result led to a less frequent initiation of ATT. The finding that fewer patients with a negative MPT64 test result received ATT could imply that clinicians had higher confidence in this new test modality and corresponds well with our previously reported high negative predictive value of the MPT64 test 11 , 12 , 27 . The poor negative predictive value of both mycobacterial culture and GeneXpert means that clinicians really cannot trust negative results.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, 22% of the non-TB patients received ATT incorrectly. Our patients were classified based on a composite reference standard, which mimicked clinical practice in the low resource setting, where patients are often treated for presumptive EPTB without microbiological confirmation 11 , 12 , 27 . The clinicians did not, however, use our case definition when diagnosing patients, but followed national guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation